Rocks and Minerals - DK Publishing, Inc. (London : Dorling Kindersley Limited, 2025)
"See how rocks form, find out what minerals are, and explore the hundreds of uses we have for them."--Provided by publisher
Rocky earth -- A volcanic beginning -- Making of a rock -- Igneous rock -- Sedimentary rock -- Metamorphic rock -- Rocks from space -- Hidden beauty -- Breakdown -- Carving a path -- Crystals -- What agem! -- Precious metals -- Get that metal! -- Rocks in art -- Using rocks -- Building rocks -- A touch of mystery -- History in a rock -- Hunting for rocks -- What does it make? -- What's this? -- A safe path -- Facts match -- Hunt that treasure!.
Includes index
"Open your eyes to a world of discovery."-- Cover.
"Dig down deep to uncover the treasures that lie beneath your feet."-- Back cover.
Keywords: Rocks -- Juvenile literature; Minerals -- Juvenile literature; Illustrated works; Informational works